The Only Good Indians [compact disc, unabridged] - Jones, Stephen Graham, 1972- (Simon & Schuster Audio, 2020)
Four American Indian men from the Blackfeet Nation, who were childhood friends, find themselves in a desperate struggle for their lives, against an entity that wants to exact revenge upon them for what they did during an elk hunt ten years earlier by killing them, their families, and friends.